2018
DOI: 10.1080/17434440.2018.1483237
|View full text |Cite
|
Sign up to set email alerts
|

International experience with minocycline, EDTA and ethanol lock for salvaging of central line associated bloodstream infections

Abstract: Our study suggests that M-EDTA-EtOH lock therapy may be an effective intervention to salvage long-term CVCs in the setting of CLABSI/CRBSI and hemodialysis cancer patients with limited vascular access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In conclusion, ALT may be a treatment option for patients with infected implantable CVCs and limited options for vascular access in conjunction with systemic antibiotic therapy. Several antiseptic solutions such as ethanol or combinations of antibiotics with antiseptic solutions have been tested in smaller studies in patients with bacteremia [223][224][225][226]. In a randomized study using either ethanol 70% or saline in 94 children with cancer as treatment or secondary prophylaxis for CLABSI, ALT did not prevent CLABSI treatment failure and it increased CVC occlusion [224].…”
Section: Antibiotic Lock Therapymentioning
confidence: 99%
“…In conclusion, ALT may be a treatment option for patients with infected implantable CVCs and limited options for vascular access in conjunction with systemic antibiotic therapy. Several antiseptic solutions such as ethanol or combinations of antibiotics with antiseptic solutions have been tested in smaller studies in patients with bacteremia [223][224][225][226]. In a randomized study using either ethanol 70% or saline in 94 children with cancer as treatment or secondary prophylaxis for CLABSI, ALT did not prevent CLABSI treatment failure and it increased CVC occlusion [224].…”
Section: Antibiotic Lock Therapymentioning
confidence: 99%
“…This review was designed in the view to investigate the prospects of recommending the systematic application of ALS against CRBSI for HD patients as an alternative to catheter removal. Catheter removal and exchange is a common practice for the treatment ofCRBSI (Böhlke et al, 2015) which can be quite challenging for patients on regular catheterizations such as HD patients, cancer patients or patients on parenteral nutrition (Hachem et al, 2018). ALS treatment is considered promising for systematic application as it appears to have not only significant effect on CRBSI rates (Sun et al, 2020) but also presents other considerable advantages such as cost-effectiveness (Leistner et al, 2014;Winnicki et al,2017) and anti-biofilm properties.…”
Section: Discussionmentioning
confidence: 99%
“…Quirt et al in a more recent study on pediatric intestinal failure patients reported that according to their preliminary findings 4% tetrasodium EDTA solution effectivelyreduced catheter-related bloodstream infections and catheter flow (Quirt et al 2021). EDTA (ethylenediaminetetraacetic acid) as the main component of cathasept and a chelating agent with known antimicrobial/anticoagulant/antibiofilm and blood vessel protective activity (Song & Zhang, 2020) has been extensively studied as a lock solution candidate (Hachem et al, 2018;Dang et al, 2019). More specifically, Dang et al in their meta-analysis estimated that EDTA is the most effective against CRBSI and exit-site infection among 13 different lock solutions at a rate of 84.4%.…”
Section: Discussionmentioning
confidence: 99%